Implementing Yusuf Al-Qaradawi’s Fiqh Al-Bi’ah Values to Strengthen Environmental Literacy at UIN Raden Mas Said Surakarta - Didiek Noeryono Basar; Antis Rachmayanti; Ahmad Nurrozaq Murbayanto (MUSLIM HERITAGE, 2026)
Environmental issues in Islamic higher education institutions have encouraged the importance of strengthening environmental literacy based on Islamic ecological values. This study aims to examine the application of ecological values in Yusuf al-Qardhawi’s Fiqh al-Bi’ah as a conceptual foundation for the development of environmental management literacy in Islamic universities, with a case study of the “Pijar Semesta” Waste Bank at UIN Raden Mas Said Surakarta. Using a qualitative descriptive method with a case study approach to understand how Islamic values are implemented in environmental management at Islamic universities. Data were collected through in-depth interviews, participatory observation, and document analysis of administrators, students, and supporting documents. Data analysis was conducted using the interactive model by Miles, Huberman, and Saldana. The research results indicate that the implementation of Yusuf al-Qaradawi’s Fiqh al-Bi’ah in the “Pijar Semesta” Waste Bank program successfully integrates modern environmental management principles with Islamic spiritual values. The management stages from organizational formation, outreach, customer registration, sorting, deposit, weighing, to reporting reflect the application of the values of trust (amanah), justice, responsibility, balance (mizan), and the spirit of mutual aid (ta’awun). This program not only yields ecological benefits through waste reduction and improved campus cleanliness but also has educational and spiritual impacts by fostering awareness among the academic community of their role as stewards in preserving the earth. Therefore, this study recommends strengthening the integration of Islamic ecological values into the curriculum, expanding cross-institutional collaboration, and developing digital innovations to realize a green campus based on faith, knowledge, and action. Abstrak Permasalahan lingkungan di perguruan tinggi Islam mendorong pentingnya penguatan literasi lingkungan berbasis nilai-nilai ekologis Islam. Penelitian ini bertujuan mengkaji penerapan nilai-nilai ekologis dalam Fiqh al-Bi’ah Yusuf al- Qardhawi sebagai landasan konseptual bagi pengembangan literasi manajemen lingkungan di perguruan tinggi Islam, dengan studi kasus pada Bank Sampah “Pijar Semesta” UIN Raden Mas Said Surakarta. Menggunakan metode deskriptif kualitatif dengan pendekatan studi kasus untuk memahami bagaimana nilai-nilai Islam diimplementasikan dalam pengelolaan lingkungan Perguruan Tinggi Islam. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumentasi terhadap pengelola, mahasiswa, serta dokumen pendukung. Analisis data dilakukan menggunakan model interaktif Miles, Huberman, dan Saldana. Hasil penelitian menunjukkan bahwa implementasi Fiqh al-Bi’ah Yusuf al-Qaradawi dalam program Bank Sampah “Pijar Semesta” berhasil mengintegrasikan prinsip-prinsip manajemen lingkungan modern dengan nilai-nilai spiritual Islam. Tahapan pengelolaan mulai dari pembentukan organisasi, sosialisasi, pendaftaran nasabah, pemilahan, penyetoran, penimbangan, hingga pelaporan mencerminkan penerapan nilai amanah, keadilan, tanggung jawab, keseimbangan (mizan), serta semangat tolong-menolong (ta’awun). Program ini tidak hanya memberikan dampak ekologis melalui pengurangan sampah dan peningkatan kebersihan kampus, tetapi juga berdampak edukatif dan spiritual dengan menumbuhkan kesadaran sivitas akademika akan peran sebagai khalifah dalam menjaga kelestarian bumi. Oleh karena itu, penelitian ini merekomendasikan penguatan integrasi nilai-nilai ekologis Islam dalam kurikulum, perluasan kolaborasi lintas lembaga, serta pengembangan inovasi digital guna mewujudkan green campus berbasis iman, ilmu, dan amal.